2020
DOI: 10.7150/jca.42900
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog/Gli1 Signaling Pathway Regulates Cell Migration and Invasion via Induction of Epithelial-to-mesenchymal Transition in Gastric Cancer

Abstract: Background:The aberrant activation of the Sonic hedgehog (Shh) signaling pathway is involved in progression of several types of cancer, including gastric cancer (GC). However, it remains uncertain whether it also plays a critical role in promoting cancer initiation and progression by inducing epithelial-to-mesenchymal transition (EMT) in GC. Thus, the aim of the present study was to determine whether the Shh pathway is involved in GC, and to investigate the function of the Shh pathway in the induction of EMT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Our results corroborate those of Yang et al [64] in the sense that Shh inhibition was produced after HDAC6 silencing, as they demonstrated that HDAC6 was upregulated in glioma stem cells compared to non-stem tumor cells, and that HDAC6 inhibition downregulated Gli1, Ptch1, and Ptch2 expression and activity in glioma stem cells. A decrease in the Shh pathway decreases cell migration and reverses EMT in lung cancer [65] and gastric cancer [47]. We have also demonstrated these effects after HDAC6 silencing in glioblastoma.…”
Section: Hdac6 Silencing In Glioblastoma Cell Linessupporting
confidence: 60%
See 1 more Smart Citation
“…Our results corroborate those of Yang et al [64] in the sense that Shh inhibition was produced after HDAC6 silencing, as they demonstrated that HDAC6 was upregulated in glioma stem cells compared to non-stem tumor cells, and that HDAC6 inhibition downregulated Gli1, Ptch1, and Ptch2 expression and activity in glioma stem cells. A decrease in the Shh pathway decreases cell migration and reverses EMT in lung cancer [65] and gastric cancer [47]. We have also demonstrated these effects after HDAC6 silencing in glioblastoma.…”
Section: Hdac6 Silencing In Glioblastoma Cell Linessupporting
confidence: 60%
“…Although we detected overexpression of Gli1 in the three tumor cell lines, by means of the luciferase assay, we observed that this pathway was only active in the U87MG line. This result contrasts with the fact that the Shh pathway promotes EMT [47], as it is precisely the U87MG line, the most epithelial of the three glioblastoma cell lines, that presents an active Shh pathway. However, T98G cells have been shown to be activated with recombinant Shh treatment but not inhibited after GANT61 treatment [48], which we believe reinforces our results.…”
Section: Expression Of Hdac6 and Mesenchymal And Autophagic Markers In Glioblastoma Samples And Cell Linesmentioning
confidence: 58%
“…Wnt signaling is constitutively active in 30% of GC cases [ 7 ], and Hh signaling is aberrantly active in GC [ 18 ]. These findings implicate the importance of both pathways in gastric tumorigenesis and progression.…”
Section: Resultsmentioning
confidence: 99%
“…Hh signaling inhibition leads to the increased expression of E-cad and decreased expression of VIM, whereas Hh signaling activation has the opposite effects. Overall, these results indicate that Hh signaling activation induces EMT, which in turn enhances GC progression and metastasis [ 18 ]. In this study, we found that cells transfected with miRNA-150 mimics exhibited increased activation of the Hh signaling pathway and promotion of EMT, whereas cells transfected with miRNA-150 inhibitors displayed suppression of Hh signaling and inhibition of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of actin cytoskeleton is correlated with migration and invasion of cancer [ 29 ], kinesin superfamily protein 2A, a key protein in this signaling pathway, playing the role of oncogenes in a variety of cancers [ 30–32 ]. The Hedgehog signaling processes play a significant part in the development of chronic gastritis to GC [ 33 ]; it also promotes the growth of GC cells [ 34 ] and improves the ability of migration and invasion [ 35 ]. The CAM pathway is related to tumor angiogenesis, invasion and metastasis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%